ANALISIS TEMA DALAM NOVEL THE FAULT IN OUR STARS KARYA JOHN GREEN - NIODE, SANTI HUSAIN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT As the requirement to accomplish the Bachelor Degree in English Literature at Faculty of Humanities in Sam Ratulangi University, this research entitled â€œAnalisis Tema Dalam Novel The Fault In Our Stars karya John Greenâ€ is completed and submitted. The aims of this research are to identify, classify and analyze the theme in the novel The Fault in Our Stars through the characters, plot and setting. The author uses the theory of Stanton (1965) to analyze the major theme in the novel The Fault in Our Stars through the characters, plot and setting. Intrinsic approach is used to understand the characters through physical interaction, is the thoughts and problems that occur in their lives. Understanding the plot is through the sequence of events that happen and understanding the setting is through the time and place where the story takes place, including is describing a situation or object. The results of this research show that the novel The Fault In Our Stars is a novel with a theme on teensâ€™ struggle against cancer, who have a passion for life. This can be seen through the characters, plot and setting in The Fault in Our Stars. Â  Keywords: Theme, Struggle, and TheFault in Our Stars